Orthodoxy and Heresy in the Thought of Nūr al-Dīn al-Rānīrī : Shaṭaḥāt, Takfīr, and the Boundaries of Shariah - Arfan Arfan; As'ad As'ad; Edi Kurniawan; Massuhartono Massuhartono; Ghina Nabilah Efendi; Mukhlas Nugraha (Justicia Islamica, 2025)
The theological debate in Aceh in the 17th century, particularly the accusations of heresy and infidelity directed by Nūr al-Dīn al-Rānīrī against the Wujudiyah group, reflected the tension between shariah, sufism, and creed. This issue is relevant to revisit because it is not only an essential part of the intellectual history of Islam in the archipelago, but also has strong resonance in contemporary takfīr discourse that impacts the religious practices and socio-legal order of Muslims. This study aims to analyse al-Rānīrī's accusations through the parameters of shariah, particularly in relation to shaṭaḥāt (ecstatic expressions), while also examining its significance in modern debates regarding the limits of faith and the practice of excommunication. Using a literature review method and al-Fatḥ al-Mubīn as the primary source, this study found that al-Rānīrī's verdict was based on the assumption that Wujudiyah rejected the obligations of prayer and fasting. However, a textual analysis of Hamzah Fansuri's thought showed that what is meant was only the condition of Sufis in a state of unconsciousness, which in fiqh is considered a matter of khilafiah (disagreement). Therefore, the accusations of bid'ah and kufr do not have sufficient legal legitimacy. This finding confirms that the discourse of takfīr is not only a historical problem, but also has significant socio-legal implications in contemporary times, both through institutional fatwas and the narratives of transnational groups that have the potential to give rise to stigmatisation and social conflict.